Disclosure of Risk Factors on Prospectus and Initial Public Offerings (IPO) Performance: Evidence from Indonesia - Kuswanto, Randy (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 15 No 1 (2020), 2020)
The purpose of this study is to investigate how risk information disclosed in prospectus influences the initial returns of initial public offerings (IPOs) in Indonesia. This study collected 62 sample IPOs offered in the Indonesian Stock Exchange from 2017–2018. Ordinary least squares was performed to test the association between risk disclosure and initial returns. Results indicate that prospectus provides risk information associated with initial returns. Both qualitative and quantitative dimensions have a significant negative impact on the initial returns. It can be concluded that risk information has an important role in the underpricing phenomenon. The study has extended the available literature by investigating risk disclosure from a dual perspective. Moreover, qualitative and quantitative assessments both have a direct impact on the initial returns and must be considered in investment decision making. Keywords: Risk, IPO, underpricing, initial returns